Peningkatan Kemampuan Pemecahan Masalah Matematis dan Kemandirian Belajar Siswa Menggunakan Model Pembelajaran Means End Analysis - Asih, Nur; Ramdhani, Sendi (Department of Mathematics Education Program IPI Garut, 2019)
Tujuan penelitian adalah untuk mengetahui apakah peningkatan kemampuan pemecahan masalah matematis siswa yang menggunakan model pembelajaran Means End Analysis (MEA) lebih baik dari pada konvensional, untuk mengetahui sikap kemandirian belajar siswa terhadap pembelajaran matematika menggunakan model pembelajaran Means End Analysis (MEA), dan untuk mengetahui hambatan siswa dalam menyelesaikan soal-soal kemampuan pemecahan masalah matematis. Metode penelitiannya adalah eksperimen kuasi dan desain penelitiannya Nonequivalent control group design. Populasi dalam penelitian ini adalah seluruh siswa kelas XI SMA PASUNDAN CIKALONGKULON dengan sampel sebanyak dua kelas. Teknik pengambilan sampel menggunakan teknik purposive sampling. Kelas XI MIPA-3 sebagai kelas eksperimen dan kelas XI MIPA-1 sebagai kelas kontrol. Instrumen berupa tes kemampuan pemecahan masalah matematis, angket dan wawancara. Berdasarkan hasil analisis data, peningkatan kemampuan pemecahan masalah matematis siswa yang menggunakan model pembelajaran Means End Analysis (MEA) lebih baik dari konvensional. Hasil angket siswa kelas XI MIPA-3 memperoleh hasil hampir seluruhnya positif respon siswa terhadap model pembelajaran Means End Analysis (MEA). The purpose of this research is to find out whether the improvement of students 'mathematical problem-solving abilities using the Means-End Analysis (MEA) learning model is better than conventional learning, to determine the attitudes of students' learning independence towards mathematics learning using the Means-End Analysis (MEA) learning model, and to find out the obstacles of students in solving problems mathematical problem-solving abilities. The research method is a quasi-experiment, and the research design is Nonequivalent control group design. The population in this study were all students of class XI SMA PASUNDAN CIKALONGKULON with a sample of two classes. The sampling technique uses a purposive sampling technique. Class XI MIPA-3 as an experimental class and class XI MIPA-1 as a control class. The instruments were in the form of tests of mathematical problem-solving abilities, questionnaires, and interviews. Based on the results of data analysis, the improvement of students' mathematical problem-solving abilities using the Means-End Analysis (MEA) learning model is better than conventional. The results of the XI MIPA-3 class questionnaire obtained almost entirely positive student responses to the Means-End Analysis (MEA) learning model.